2017
DOI: 10.9734/bjast/2017/33635
|View full text |Cite
|
Sign up to set email alerts
|

Assessing of Farmers’ Opinion towards Floating Agriculture as a Means of Cleaner Production: A Case of Barisal District, Bangladesh

Abstract: Aims: Bangladesh, as a low-lying country, is vulnerable to global climate change and affected by floods and water logging. Hence, the country needs to adopt sufficient adaptation strategies which are based on local people traditional knowledge and locally available materials; hence, floating agriculture is that type of agriculture. Through this article we examine the floating agriculture related farmers opinion towards floating agriculture as a means of cleaner production Original Research Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
5
17
0
Order By: Relevance
“…In the study area, fifty-eight percent respondents use their own fund for floating gardening whereas 34% collect loan from bank and NGOs. This result is in the line with the result found by MoEF (2005) and Hasan et al (2017). Requirement of lower investment for floating gardening might be the responsible factor for that pattern of resource allocation.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In the study area, fifty-eight percent respondents use their own fund for floating gardening whereas 34% collect loan from bank and NGOs. This result is in the line with the result found by MoEF (2005) and Hasan et al (2017). Requirement of lower investment for floating gardening might be the responsible factor for that pattern of resource allocation.…”
Section: Resultssupporting
confidence: 92%
“…Average use of fertilizers was 284 kg ha -1 . The proportional investment on seed/seedling, fertilizers and insecticides & pesticides were very low (Islam and Atkins, 2007;Irfanullah, 2009;Chowdhury and Moore, 2017) although Hasan et al (2017) and Islam et al (2019) claimed about no use of chemical fertilizers for floating gardening. The smart use of different organic matters and required essential nutrients for the plants during floating beds preparation might confirm the expected growth of the plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a study Faroque and Takeya [32], found that education level, farming experience, farm size, family size, fertilizer use and communication exposure had an influence on perceptions of integrated soil fertility and nutrient management. Through another study, Hasan et al, [33] found that farmer"s age had an influence on the opinion towards floating agriculture. In the developing world, farm size may be considered as an important determinant that directly influences education and other physical facilities that develop knowledge and experience in farming and improved communication skills.…”
Section: Influence Of Farmers' Characteristics Upon Their Knowledgementioning
confidence: 98%